Mobility and fear of falls measuring tools to predict falls risk among Malaysian community dwelling older adults - Devinder Kaur Ajit Singh,; Ng, Ee San; Ng, Cheah Ping; Nor Najwatul Akmal Ab Rahman,; Sheela Bai Pannir Selvam, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Falls is a global health issue among older adults. Identifying measuring tools that can predict falls risk among older adults can assist in early falls risk detection and prevention. Best measuring tools that can predict falls risk among Malaysian community dwelling older adults is not known. The objective of our study was to determine if Timed Up and Go (TUG) test and Activities-Specific Balance Confidence (ABC) scale could be used as a falls risk predictor tools among Malaysian community dwelling older adults. Hundred and six (n = 106) community dwelling older adults who were attending Klinik Kesihatan Cheras participated in this cross sectional study. Falls incidence in the past one year was obtained from the participants. TUG test was performed and ABC scale was administered. Data was analysed using binomial logistic regression and receiver operating curves (ROC). The cut off values identified for TUG test and ABC scale were 9.02 seconds (area under the curve, AUC was 0.711; 95% CI 0.577-0.844) and 82.81% (area under the curve, AUC was 0.682; 95% CI 0.562-0.802) respectively. Hence, older adults with a score of above 9.02 seconds for TUG test and a score of below 82.81% for ABC scale were noted to have a higher risk of falls. Results of this study demonstrated that both TUG test (p < 0.001) and ABC scale (p < 0.01) were significant predictors of falls risk. Our study results indicated that both mobility (TUG test) and fear of falls (ABC scale) measuring tools, with the present cut off values can be used to identify community dwelling older adults who are at a higher risk of falls. Identifying older adults with higher risk of falls can assist the health professionals to optimise falls prevention and management approaches.